Protective Efficiency of Railway Arbor-Shrub Windbreak Forest Belts in Gobi Regions: Numerical Simulation and Wind Tunnel Tests - Zhang, Kai; Qu, Jianjun; Zhang, Xingxin; Zhao, Liming; Li, Sheng (Frontiers in Environmental Science, 2022)
The railways in the Gobi area have serious sand hazards. To prevent these hazards and ensure operational safety, plant-based sand prevention is a fundamental measure for the prevention and control of railway wind-sand hazards. This study considers the protective windbreak forest belts along the Lan-Xin Railway, Northwest China as the study area and evaluates its protective benefits from the perspectives of windproof efficiency and sand control efficiency using numerical simulations and wind tunnel testing. Our results show that the disrupting effect of the three shelterbelt rows on the airflow was significantly enhanced, and the wind velocity profile began to change at 2H. As the airflow continued to move forward, the wind velocity profile gradually deviated from the logarithmic law, and an obvious turning point appeared at 13H behind the forest belt. Under different incoming wind velocities, the maximum wind protection efficiency of the three shelterbelt rows appeared at 5H on the leeward side. The maximum wind protection efficiencies in the numerical simulation were 95.1%, 90.4%, and 88.6%, respectively. The minimum value appeared at 15H on the leeward side, and the minimum wind protection efficiencies were 58.3%, 53.1%, and 47.1%, respectively. The maximum wind protection efficiencies in the tunnel test were 94.3%, 90.1%, and 86.5%, and the minimum value appeared at 15H on the leeward side. As the wind velocity increased, the efficiency of wind protection tended to decrease. The sand control efficiencies of the shelterbelt were 93.8%, 91.6%, and 88.1%, and as the wind velocity increased, the sand control efficiency continued to decrease. In general, the forest belt had a significant effect on reducing the sand flux density, especially below the forest belt height, which can effectively control the wind and sand disasters in some Gobi areas along the Lan-Xin Railway.